Microinfarcts in an older population‐representative brain donor cohort (MRC CFAS): Prevalence, relation to dementia and mobility, and implications for the evaluation of cerebral Small Vessel Disease. (28th October 2016) - Ince, P. G.; Minett, T.; Forster, G.; Brayne, C.; Wharton, S. B.; ,
Abstract : Introduction: Microinfarcts, small ischaemic foci common in ageing brain, are associated with dementia and gait dysfunction. We determined their relationship with dementia, mobility and cerebrovascular disease in an older population‐representative brain donor cohort. These data on microinfarcts were evaluated in relation to pathological assessments of clinically significant cerebral small vessel disease (SVD). Methods: Microinfarcts were assessed in the MRC Cognitive Function and Ageing Study (n = 331). Nine brain areas were staged according to the number of areas affected. Results: 36% of brains showed at least 1 microinfarct. Higher cortical microinfarct stage was associated with dementia at death (OR 1.41, 95% CI 1.02; 1.96, P = 0.038), whilst cortical and subcortical microinfarct stages were associated with impaired mobility (OR 1.36, 95% CI 1.05–1.74; P 0.018) and falls (OR 1.96, 95% CI 1.11–3.43; P = 0.02). Adding data on microinfarcts to a definition of SVD, based on white matter lesions (WMLs), lacunes and significant arteriosclerosis, were assessed by comparing area under ROC curve (AUC) with and without microinfarcts. SVD was significantly related to dementia status with or without inclusion of microinfarcts. Modelling potential pathological definitions of SVD to predict dementia or impaired mobility indicated optimal prediction using combined assessment of WMLs, lacunes and microinfarcts. Conclusion: Cortical (dementia) and subcortical microinfarcts (impaired mobility) are related to diverse clinical outcomes. Optimal pathological assessment of significant SVD in brain ageing is achieved based on WMLs, lacunes and microinfarcts and may not require subjective assessment of the extent and severity of arteriosclerosis. Abstract : Microinfarcts are common in the brains of elderly individuals correlating with cognitive impairment, impaired mobility and falls. They should be included in the neuropathological assessment of small vessel disease.